Indexed resource auction multiple access (I-RAMA) : a new medium access scheme for third generation wireless networks. - Barrantes Sliesarieva, Elena Gabriela 1967- (Boca Ratón, Fla. : [editor no identificado], 1995)
Tesis (Magister Scientiae)--Florida Atlantic University, 1995.
Keywords: TELECOMUNICACIONES; SISTEMAS MOVILES DE COMUNICACION; REDES DE COMPUTADORAS